Exercise Training Improves Insulin Release During Glucose Tolerance Testing in Stable Chronic Heart Failure Patients. Issue 1 (January 2015) - Stevens, An L.M.; Hansen, Dominique; Herbots, Lieven; Wens, Inez; Creemers, An; Dendale, Paul; Eijnde, Bert O.
<x xml:space="preserve">Abstract</x> PURPOSE: Chronic heart failure (CHF) patients often present with (pre)diabetes, which negatively influences prognosis. Unlike the proven effect of exercise on glucose regulation in the general population, its effect in CHF is unclear. Therefore, this study aimed at investigating the effect of exercise training on glucose regulation in stable CHF patients. METHODS: Twenty-two CHF patients were randomized into training (EX, n = 15) and control (CON, n = 7) groups. Before and after a 12-week training intervention involving endurance and resistance training, glucose tolerance (2-hour oral glucose tolerance test), exercise tolerance (cardiopulmonary exercise test), muscle strength (isokinetic dynamometer), heart function (echocardiography), glycated hemoglobin, body composition (dual-energy x-ray absorptiometry), and quality of life (EQ5D) were assessed. RESULTS: At baseline, glucose levels 2 hours after glucose intake were elevated in both groups. Whereas area under the glucose curve did not change, area under the insulin curve decreased following training (EX, −13 ± 23% vs CON, +22 ± 33%; P < .05). Changes in the ratio of mitral peak velocity of early filling/early diastolic mitral annular velocity and waist-to-hip fat mass ratio were related to changes in the insulin curve. Exercise training resulted in improved oxygen uptake at the second ventilatory threshold (EX, +10 ± 5% vs CON, −8 ± 5%; P < .05) and isokinetic strength endurance of the upper leg (EX, +25 ± 9% vs CON, −6 ± 5%; P < 0.05). Lean body tissue was increased by 2.2 ± 0.5% in EX versus 0.2 ± 0.6% in CON (P < .05). CONCLUSION: Our data suggest that exercise training attenuates worsening of glucose regulation typically seen in a stable CHF population.